Investigating Adherence to COVID-19 Vaccination and Serum Antibody Concentration among Hospital Workers—The Experience of an Italian Private Hospital - Guglielmo Forgeschi (MDPI AG, 2021)
SARS-CoV-2 transmission has been high, especially among healthcare workers worldwide during the first wave. Vaccination is recognized as the most effective approach to combat the pandemic, but hesitation to get vaccinated represents an obstacle. Another important issue is the duration of protection after administration of the full vaccination cycle. Based on these premises, we conducted a study to evaluate vaccination adherence and the anti-S antibodies levels among hospital workers, from January to March, 2021. To assess adherence, an anonymous questionnaire was used. Anti-S antibody levels were obtained from the monitoring serological sample database. In total, 56.2% of the unvaccinated people did not report a previous infection from COVID-19. Among those who have not been vaccinated, 12.5% showed distrust against the vaccine, 8.3% stated to have received contraindications to the vaccination, and 6.3% did not report any choice. Analyzing anti-S antibody levels, only one person was found to have a value below the lower cut-off, two weeks, and three months after receiving their second dose. One was below the cut-off after two weeks, and then above the same cut-off after three months. The results of our survey should be seen as a stimulus to further sensitize hospital staff to the importance of vaccination and pay attention to anti-S antibody levels monitoring.